Clinical and laboratory impact of concomitant syphilis infection during acute HIV. Issue 6 (17th March 2021) - Chan, P; Colby, DJ; Kroon, E; Sacdalan, C; Pinyakorn, S; Paul, R; Robb, M; Valcour, V; Ananworanich, J; Marra, C; Spudich, S
Abstract : Introduction: Cognitive impairment has been reported in people living with HIV‐1 (PLWH) with prior syphilis, while PLWH who present with incident syphilis have reduced blood CD4 T‐lymphocyte and elevated HIV‐1 RNA levels. However, the clinical, virological and neurocognitive effects of syphilis during acute HIV‐1 (AHI) remain unknown. Methods: Pre‐antiretroviral therapy laboratory outcomes and neurocognitive performance in a four‐test battery in the SEARCH10/RV254 AHI cohort were compared according to syphilis status, determined by serum Treponema pallidum haemagglutination (TPHA), Venereal Disease Research Laboratory (VDRL) and syphilis treatment history. Impaired cognitive performance was defined as having z ‐scores ≤ −1 in at least two tests or ≤ −2 in at least one test. Results: Out of 595 AHI participants (97% male, median age of 26 years and estimated duration of HIV‐1 infection of 19 days), 119 (20%) had history of syphilis (TPHA‐positive), of whom 51 (9%) had untreated syphilis (TPHA‐positive/VDRL‐positive/without prior treatment). Compared with those without syphilis (TPHA‐negative), individuals with untreated syphilis had higher CD8 T‐lymphocyte levels but not higher plasma HIV‐1 RNA or lower CD4 T‐lymphocyte levels. Taking into account estimated duration of HIV‐1 infection ( P < 0.001), and later Fiebig stages (III–V) ( P < 0.001), those with untreated syphilis had higher CD8 T‐lymphocyte levels ( P = 0.049). Individuals with any syphilis (TPHA‐positive), but not untreated syphilis, had higher odds of impaired cognitive performance than those without ( P = 0.002). Conclusions: During AHI, individuals with any history of syphilis (TPHA‐positive) had poorer cognitive performance than those without syphilis. However, syphilis was not associated with worsened HIV disease measures as described in chronic infection.